2007
DOI: 10.1111/j.1471-4159.2007.04898.x
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cell‐derived neural precursors as a continuous, stable, and on‐demand source for human dopamine neurons

Abstract: Human embryonic stem (hES) cells can be guided to differentiate into ventral midbrain-type neural precursor (NP) cells that proliferate in vitro by specific mitogens. We investigated the potential of these NP cells derived from hES cells (hES-NP) for the large-scale generation of human dopamine (DA) neurons for functional analyses and therapeutic applications. To address this, hES-NP cells were expanded in vitro for 1.5 months with six passages, and their proliferation and differentiation properties determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 47 publications
1
58
0
1
Order By: Relevance
“…However, the expression levels of three germ layer markers were significantly reduced in late passage. Ko et al (2007) also reported that the degree of hESC differentiation varied depending on the passage number of undifferentiated hESCs in HSF-6 hES cell line. These results indicated that although long-term cultured hESCs retained somewhat their pluripotency, they also possessed a tendency to maintain an undifferentiated state rather than to differentiate.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression levels of three germ layer markers were significantly reduced in late passage. Ko et al (2007) also reported that the degree of hESC differentiation varied depending on the passage number of undifferentiated hESCs in HSF-6 hES cell line. These results indicated that although long-term cultured hESCs retained somewhat their pluripotency, they also possessed a tendency to maintain an undifferentiated state rather than to differentiate.…”
Section: Discussionmentioning
confidence: 99%
“…The hiPSCs and hESCs used in this study are listed in Tables 1 and 2. Undifferentiated hiPSCs and hESCs were propagated on MEF feeder and differentiated toward midbrain-type NPCs on feeder layers of MS5 and subsequently on MS5-SHH as previously described (17,45). bFGF (20 ng/ml) was supplemented during the first week of the coculture period.…”
Section: Methodsmentioning
confidence: 99%
“…Since individual ES cell (ESC) and iPSC lines are known to have different propensities to differentiate into specific cell lineages (11)(12)(13), we first optimized in vitro differentiation methods to generate neuronal precursor cells (NPCs) and DA neurons from these diverse hiPSC lines. Based on previous studies showing efficient neural induction and/or proliferation of NPCs on different feeder cells (14)(15)(16)(17)(18)(19), we first optimized the stromal coculture method to ensure efficient neural induction from hiPSC and hESC lines. As schematized in Figure 1A, undifferentiated hiPSCs maintained on mouse embryonic fibroblasts (MEFs) were sequentially cocultured onto MS5 feeder cells and MS5 stably expressing sonic hedgehog (MS5-SHH).…”
Section: Induction Of Hipscs Into Primitive Neuroepithelial Cell Typesmentioning
confidence: 99%
“…These neurons were transplanted into the nigral-stratial pathway with negative consequences including proliferation following transplantation and terotoma formation (Brederlau et al, 2006). Differentiation of H9 hESCs on a SHH secreting M5S stromal feeder layer with bFGF lead to no teratoma formation when transplanted into the SN, but few TH+ cells survived (Ko et al, 2007). Attempts at differentiation with a bone marrow stromal cell feeder layer and FGF8/SHH lead to 40% TH+ cells but no cells survived the graft.…”
Section: Dopaminergic Differentiationmentioning
confidence: 99%